Nutritional status of elderly participants of the Hiperdia system: socio-demographic characteristics and blood pressure - Raquel Cristina Luis Mincoff; Rose Mari Bennemann; Mayra Costa Martins (Rev Rene)
Objective: to analyze the socio-demographic characteristics and stages of blood pressure associated to the nutritional status of elderly hypertensive patients included in the System of Registration and Monitoring of Hypertensive and Diabetic patient sin a Basic Health Unit. Methods: cross-sectional study with primary and secondary data collection. The nutritional status was evaluated through the body mass index and analyzed, according to socio-demographic characteristics and stages of blood pressure. To analyze the data, the chi-square test was used. Results: 250 elderly (63.6% women) were evaluated. Statistically significant association was observed between nutritional status and gender (p = 0.008), age group (p = 0.05) andstage of hypertension: optimal, normal and hypertension 1. Conclusion: the elderly assisted by the service require constant nutritional and blood pressure re-evaluation provided by the health team.